Superacid-Promoted Dual C–C Bond Formation by Friedel–Crafts Alkylation and Acylation of Ethyl Cinnamates: Synthesis of Indanones - Venkat Ramulu, Bokka; Gopi Krishna Reddy, Alavala; Satyanarayana, Gedu (Synlett, 2013)
A superacid (triflic acid) promoted dual C–C bond formation via intermolecular Friedel–Crafts alkylation (Michael addition type) and intramolecular acylation for the efficient synthesis of 3-substituted indan-1-ones is presented. This method was successful in activating ethyl cinnamates towards dual aromatic electrophilic substitution. Moreover, it enabled us to synthesize novel spirotetracyclic systems.
Keywords: cinnamates; indanones; Friedel–Crafts alkylation; acylation; superacid